Utilization and expenditure on long-acting insulin analogs among selected middle-income countries with high patient co-payment levels: Findings and implications for the future - Mainul Haque, Salequl Islam, Abdullahi Rabiu Abubakar, Ibrahim Haruna Sani, Sylvia Opanga, Zubair Mahmood Kamal, Farhana Akter, Brian Godman (Journal of Applied Pharmaceutical Science, 2021)
The number of patients with diabetes and associated complications is rising across countries including patients requiring insulin to control their diabetes. Hypoglycemia combined generally with poor control adds to the burden of diabetes. Long-acting insulin analogs were developed to reduce hypoglycemia, including nocturnal hypoglycemia, and enhance adherence, which can be a problem. These benefits have resulted in their increased use among high and high-middle income countries, which is continuing. However, concerns in middle and lower-income countries as insulin analogs are considerably more expensive than standard insulins. Biosimilars can reduce their costs. Consequently, it is important to ascertain current usage and prices of analogs across middle-income countries with high patient co-payment levels to provide future direction. Overall, limited use of insulin glargine in Kenya, up to 3.6% of total insulins in one leading hospital with prices up to 3.4 fold higher than standard insulins. Overall, limited use of insulin glargine among hospitals in Northern Nigeria and in pharmacies again due to high prices. Appreciably higher use of long-acting insulin analogs in Bangladesh enhanced by low cost biosimilars with increasing competition. Increased competition enhanced by local production can lower biosimilar costs enhancing future use of insulin glargine to the benefit of all diabetes patients requiring insulin.
Keywords: Affordability, Bangladesh, diabetes, Kenya, long-acting insulin analogs, Nigeria